Adhesive sheet roll and adhesive sheet

By using the adhesive layer clamped between the light peeling sheet and the heavy peeling sheet in the adhesive sheet roller, combined with the specific peeling force and thickness range, the deformation and tunneling of the adhesive layer in the roller form is solved, and high-quality adhesive is achieved Application of layers in flexible displays.

CN117777868BActive Publication Date: 2024-12-24아티엔스가부시키가이샤 +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311729802.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-12-27
Filing Date
2023-12-15
Publication Date
2024-12-24
Estimated Expiration
2043-12-15

AI Technical Summary

Technical Problem

In the roller form, the double-sided adhesive sheet without substrate is prone to deformation, dent or tunneling of the adhesive layer due to tension, affecting the adhesion layer and the adhered body, and is especially more serious in flexible display applications.

Method used

Design an adhesive sheet roller, with a strip-shaped adhesive sheet wound on its core, and the adhesive layer is clamped by a light peeling sheet and a heavy peeling sheet. The peeling force is within a specific range, and the thickness of the light peeling sheet is smaller than that of the heavy peeling sheet. The thickness of the adhesive layer is 5 μm to 150 μm, contains 50% to 90% of the gel fraction and an adhesive resin of 500,000 or more, and contains a (meth)acrylic acid copolymer, and forms a silicone-based mold release layer on the bonding surface.

Benefits of technology

Effectively suppress the floating, partial peeling and dent of the adhesive layer, maintain the balance and follow-up of the adhesive layer, improve the surface quality of the adhesive layer and follow-up of foreign objects, and is suitable for flexible displays to prevent tunneling and adhesive layer deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117777868B_ABST
    Figure CN117777868B_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive sheet roll and adhesive sheet for a flexible display with excellent quality. The adhesive sheet roll is an adhesive sheet roll (10) in which a long strip of adhesive sheet (3) is wound on a winding core. The adhesive sheet (3) comprises an adhesive layer (7) which is sandwiched by a light release sheet (8) and a heavy release sheet (6) and has a thickness of 5 μm to 150 μm. In the adhesive sheet (3) rolled out from an adhesive sheet roller (10), the peeling force (Pl) when peeling the light release sheet (8) from the adhesive layer (7) is 0.02 N / 25 mm to 0.30 N / 25 mm. A 50 μm PET film is attached to the exposed adhesive layer (7). The peeling force (Ph) when further peeling the heavy release sheet (6) from the adhesive layer (7) is 0.10 N / 25 mm to 0.80 N / 25 mm. Ph / Pl is set to 2 to 6, the thickness (Tl) of the light release sheet and the thickness (Th) of the heavy release sheet are set to specific ranges, and the outer side of the roll is set as the light release sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet roll having a double-sided adhesive layer without a substrate and an adhesive sheet. Background Art

[0002] A double-sided adhesive sheet without a substrate is known. This double-sided adhesive sheet is used for bonding adherends to each other, and usually an adhesive layer is sandwiched between release sheets. In addition to being produced in the form of a sheet, this adhesive sheet is sometimes also manufactured in the form of an adhesive sheet roll wound on a winding core in order to improve productivity.

[0003] With the aim of providing an adhesive sheet roller that can suppress the exposure of the paste and the generation of tunnel-shaped floating, a rolled adhesive sheet is disclosed, which is formed by winding a laminated sheet of a first peeling sheet / an adhesive layer having a shear storage elastic modulus at 120°C in a specific range / a second peeling sheet into a roll, and the roll hardness is in a specific range (Japanese Patent Gazette No. 2021-1272, Japanese Patent Gazette No. 2021-1273).

[0004] In recent years, the development of technologies for achieving large-screen displays while maintaining the size of the machine is actively underway. For example, there are foldable displays and rollable displays. The former is a foldable display that can be opened and closed freely, and the latter is a display with a rollable panel. In addition to the properties of the adhesive layer required in the past, the adhesive layer used in such a flexible display also requires bendability and resilience. Summary of the invention

[0005] [Problems to be solved by the invention]

[0006] From the perspective of productivity, double-sided adhesive sheets without substrates are required to be in the form of adhesive sheet rolls in the market. However, if the adhesive sheet is in the form of a roll, there is a problem that the adhesive layer is deformed due to the mixing of foreign matter such as dust or dirt, or that tiny bumps (dents) are generated on the adhesive layer because tension is applied to the adhesive sheet. In addition, there is the following problem: due to the tension of the adhesive sheet in the form of a roll, or when it is rolled out from the roll, a tunneling phenomenon occurs between the peeling sheet and the adhesive layer, causing peeling or floating (bubbles), leaving peeling marks on the adhesive layer.

[0007] Sometimes, due to deformation, dents or tunneling of the adhesive layer, the adhesion between the adhesive layer and the adherend decreases. In addition, when the adhesive layer is used for attaching a display component, the image quality sometimes decreases. This problem becomes a particularly serious problem in an adhesive layer designed to be applicable to a flexible device and to take into account flexibility and resilience.

[0008] The present disclosure has been made in view of the above-mentioned problems, and an object of the present disclosure is to provide an adhesive sheet roll and an adhesive sheet for a flexible display having excellent quality.

[0009] [Technical means to solve the problem]

[0010] The present disclosure provides the following adhesive sheet roll and adhesive sheet.

[0011] [1]: An adhesive sheet roll for a flexible display, wherein a long strip of adhesive sheet is wound on a core, wherein:

[0012] The adhesive sheet has an adhesive layer sandwiched by a light release sheet and a heavy release sheet and having a thickness of 5 μm to 150 μm.

[0013] In the adhesive sheet rolled out from the adhesive sheet roll, the peeling force Pl when the light peeling sheet is peeled off from the adhesive layer at a peeling angle of 180° and a peeling speed of 300 mm / min is 0.02 N / 25 mm to 0.30 N / 25 mm under an environment of 23° C. and a relative humidity of 50%,

[0014] After the light release sheet is peeled off from the adhesive layer, a 50 μm polyethylene terephthalate (PET) film is attached to the exposed adhesive layer, and the peeling force Ph when the heavy release sheet is further peeled off from the adhesive layer at a peeling angle of 180° and a peeling speed of 300 mm / min is 0.10 N / 25 mm to 0.80 N / 25 mm under an environment of 23° C. and a relative humidity of 50%,

[0015] Ph / Pl is 2 to 6,

[0016] The thickness Tl of the light release sheet is 25 μm to 100 μm.

[0017] The thickness Th of the heavy release sheet is 50 μm to 188 μm.

[0018] And the Tl is less than the Th,

[0019] The light release sheet is placed on the outside of the roll.

[0020] [2]: The adhesive sheet roll according to [1], wherein a standard deviation σ of the thickness of the adhesive sheet is 10% or less relative to the layer thickness.

[0021] [3]: The adhesive sheet roll according to [1] or [2], wherein the adhesive layer is

[0022] The gel fraction is 50% to 90% and the storage elastic modulus at -30°C is 10 MPa or less.

[0023] and an adhesive layer containing an adhesive resin having a weight average molecular weight of 500,000 or more,

[0024] The adhesive resin comprises a (meth)acrylic acid copolymer (a),

[0025] The (meth)acrylic copolymer (a) is a copolymer having a structural unit derived from an alicyclic (meth)acrylate monomer and / or a structural unit derived from a linear or branched alkyl (meth)acrylate monomer having an alkyl group having 8 to 20 carbon atoms.

[0026] [4]: The adhesive sheet roll according to any one of [1] to [3], wherein the thickness of the adhesive layer is 25 μm to 150 μm,

[0027] The adhesive force of the adhesive layer is 10 N / 25 mm to 40 N / 25 mm with respect to the polyimide substrate.

[0028] [5]: The adhesive sheet roll according to any one of [1] to [4], wherein the adhesive layer is formed using an adhesive composition containing an adhesive resin comprising a (meth)acrylic copolymer (a).

[0029] [6]: The adhesive sheet roll according to any one of [1] to [5], wherein the light release sheet and the heavy release sheet have a release layer formed of a silicone release agent on a surface that contacts the adhesive layer.

[0030] [7]: An adhesive sheet for a flexible display, which is produced by rolling out the adhesive sheet roll according to any one of [1] to [6] and performing a punching process.

[0031] [Effects of the Invention]

[0032] The present disclosure provides an excellent effect of providing an adhesive sheet roll and an adhesive sheet for a flexible display having excellent quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic perspective view showing an example of an adhesive sheet roll according to an embodiment.

[0034] Figure 2 yes Figure 1 Cross-sectional view of the II-II cut portion.

[0035] Explanation of symbols

[0036] 1: Core

[0037] 2: Foam layer

[0038] 3: Adhesive sheet

[0039] 6: Heavy peeling film

[0040] 7: Adhesive layer

[0041] 8: Light peeling

[0042] 10: Adhesive sheet roller

[0043] Ta, Th, Tl, Tt: thickness

[0044] Wa: Non-facing area DETAILED DESCRIPTION

[0045] Hereinafter, the present disclosure will be described in detail. In addition, as long as it conforms to the purpose of the present disclosure, other embodiments are of course also included in the scope of the present disclosure. In addition, the numerical range determined by using "to" in this specification includes the numerical values ​​recorded before and after "to" as the range of the lower limit and upper limit. In addition, in this specification, "film", "sheet" and "belt" are synonymous and are not distinguished according to thickness or shape. The so-called (meth)acrylic acid refers to acrylic acid or methacrylic acid. In addition, unless otherwise specified, the various components appearing in this specification can be used independently and alone, or two or more can be used in combination. The numerical values ​​determined in this specification refer to the values ​​obtained by the methods described in the embodiments.

[0046] 1. Adhesive sheet roller

[0047] The adhesive sheet roll disclosed herein (hereinafter, also referred to as the present adhesive sheet roll) is a roll sheet having a long strip of adhesive sheet (hereinafter, also referred to as the present adhesive sheet) wound on a core. The present adhesive sheet is a double-sided adhesive laminate without a substrate in which a light release sheet / adhesive layer / heavy release sheet are sequentially laminated. The present adhesive sheet roll is suitable for flexible display applications. However, it is not excluded that it can be used for applications other than the above.

[0048] The adhesive sheet roll is rolled out and cut and punched as needed. Then, after the light peeling sheet is peeled off and removed, the exposed adhesive layer is attached to the adherend, and then, the heavy peeling sheet is peeled off and removed, and the exposed adhesive layer is attached to another adherend. Through this process, the adherends are joined to each other.

[0049] The adhesive sheet roll has an adhesive sheet satisfying the following (i) to (v).

[0050] (i) The thickness of the adhesive layer is set to 5 μm to 150 μm.

[0051] (ii) In the adhesive sheet rolled out from the adhesive sheet roll, the peeling force Pl when the light release sheet is peeled off from the adhesive layer at a peeling angle of 180° and a peeling speed of 300 mm / min under an environment of 23°C and a relative humidity of 50% is 0.02 N / 25 mm to 0.30 N / 25 mm.

[0052] (iii) After peeling off the light peeling sheet from the adhesive layer, a 50 μm PET film is attached to the exposed adhesive layer. When the heavy peeling sheet is further peeled off from the adhesive layer at a peeling angle of 180° and a peeling speed of 300 mm / min at 23°C and a relative humidity of 50%, the peeling force Ph is 0.10 N / 25 mm to 0.80 N / 25 mm.

[0053] (iv) The ratio of the peel force Ph to the peel force Pl, Ph / Pl, is 2 to 6.

[0054] (v) The thickness Tl of the light release sheet is 25 μm to 100 μm, the thickness Th of the heavy release sheet is 50 μm to 188 μm, and Tl is less than Th. The light release sheet is disposed outside the roll.

[0055] The peeling force Pl of the light peeling sheet and the peeling force Ph of the heavy peeling sheet can be adjusted by the demoulding process of the sticking surface of each peeling sheet with the adhesive layer. For example, the peeling force can be adjusted according to the type of sheet and the type of the release agent applied to the substrate surface. In addition, the peeling force can be adjusted according to the coating amount of the release agent. And then, it can also be adjusted by the surface roughness of the release layer. In addition, it can also be adjusted by the adhesive composition forming the adhesive layer. When you want to reduce the value of the peeling force, it is effective to make the surface roughness coarser, increase the coating amount of the release agent, etc., and when you want to increase the value of the peeling force, just adjust it on the contrary.

[0056] The peeling force Pl of the light release sheet and the peeling force Ph of the heavy release sheet in the present disclosure are measured by the method described in the examples described later. In addition, as shown in the examples described later, the measured value of the peeling force of the structure of light release sheet / adhesive layer / PET film 50μm (G2L, manufactured by Toyobo Co., Ltd.) and the measured value of the light release sheet measured by the structure of light release sheet / adhesive layer / heavy release sheet (50μm or more) become substantially the same peeling force.

[0057] The adhesive sheet roll applies tension to the adhesive layer by winding. As a result, sometimes tiny bumps and deformations are caused in the adhesive layer. In addition, foreign matter such as dust or dirt attached to the adhesive sheet sometimes causes deformation of the adhesive layer through the heavy peeling sheet or the light peeling sheet. Furthermore, during the manufacture, storage, and transportation of the adhesive sheet roll, tunneling phenomena such as floating (bubbles) and partial peeling sometimes occur between the adhesive layer and the peeling sheet.

[0058] Deformation, dents, or tunneling of the adhesive layer can be confirmed, for example, by irradiating the adhesive sheet with light and projecting it onto a screen. In displays to which functional layers such as polarizing plates and antistatic films are attached via adhesive layers, such dents and the like affect visibility and hinder high definition.

[0059] The inventors have repeatedly conducted diligent research and found that, by satisfying the above (i) to (v) adhesive sheets, the stacking balance of the light release sheet / adhesive layer / heavy release sheet can be maintained even when a roller body is formed, and the floating and partial peeling of the adhesive layer and the release sheet can be effectively suppressed, thereby suppressing the deformation and micro-concave-convex of the adhesive layer. In addition, it is known that bubbles can be effectively suppressed even when repeatedly bent. By using this adhesive sheet, a high-quality adhesive sheet roller can be obtained even when used for flexible display applications.

[0060] By the following combination, i.e., the thickness Ta of the adhesive layer is set to 5μm to 150μm, the peeling force Pl is 0.02N / 25mm to 0.30N / 25mm, the peeling force Ph is 0.10N / 25mm to 0.80N / 25mm, and Ph / Pl is 2 to 6, and further, the thickness Tl of the light peeling sheet is 25μm to 100μm, the thickness Th of the heavy peeling sheet is 50μm to 188μm, and the light peeling sheet is set on the outside of the roll, the tunneling phenomenon can be effectively prevented and the peeling marks can be suppressed. In addition, by setting the adhesive layer to the specific range, the light transmittance and bendability can be well maintained while exerting the adhesive force.

[0061] By setting the thickness Tl of the light release sheet to a range of 25μm to 100μm, and the thickness Th of the heavy release sheet to a range of 50μm to 188μm, and setting the relationship of Tl < Th, the light release sheet is arranged on the outside of the roll in the present adhesive sheet roll, which can give the heavy release sheet a cushioning property and suppress the occurrence of dents caused by foreign matter or shaking during transportation. In addition, by arranging the light release sheet, which is thinner than the heavy release sheet, on the outside of the roll, the light release sheet and the adhesive layer can be effectively prevented from floating up, and the followability of the adhesive layer can be improved, effectively improving the surface unevenness of the adhesive layer or the followability of the adhesive layer to tiny protrusions caused by foreign matter located outside the present adhesive sheet. In addition, by combining the heavy release sheet with the light release sheet, the deformation of the adhesive layer can be suppressed.

[0062] Furthermore, by setting the peeling force Pl to 0.02N / 25mm to 0.30N / 25mm, tunneling phenomena such as floating and partial peeling of the light peeling sheet and the adhesive layer can be effectively suppressed. In addition, in the relationship between the peeling force Ph and the peeling force Pl, by setting Ph to 0.10N / 25mm to 0.80N / 25mm within the range of Ph / Pl satisfying the range of 2 to 6, the phenomenon of forced separation of the adhesive layer and the heavy peeling sheet can be effectively suppressed. In addition, the outer diameter is the outer diameter when the foam layer and the like are included in the case of including the foam layer and the like described later.

[0063] exist Figure 1An example of a schematic diagram of the adhesive sheet roll is shown in FIG. The adhesive sheet roll 10 has a long adhesive sheet 3 wound on a core 1. The core 1 can be cylindrical or columnar. The outer diameter (diameter) of the core 1 is, for example, about 100 mm to 1000 mm. The width of the adhesive sheet roll is, for example, about 100 mm to 3000 mm, and the winding length of the adhesive sheet is, for example, about 10 m to 3000 m.

[0064] Figure 2 yes Figure 1 The II-II section of the cut section. Figure 2 As shown, the adhesive sheet 3 rolled out from the adhesive sheet roll 10 has an adhesive layer 7 sandwiched by a light release sheet 8 and a heavy release sheet 6. The adhesive sheet 3 is a laminate without a substrate, and the release surface of the light release sheet 8 is arranged on the adhesive layer 7 side, and the release surface of the heavy release sheet 6 is arranged on the adhesive layer 7 side. Figure 2 As shown, it is preferred that there are non-adhesive layer forming areas at both ends of the light peeling sheet 8 and the heavy peeling sheet 6 in the width direction. It is also possible to configure a spacer between the peeling sheets in the non-adhesive layer forming area. The spacer can be configured in any form such as linear or dot along the long side direction of the end. By providing the spacer, the facing distance can be maintained or the exposure of the adhesive layer can be suppressed. The non-facing area Wa can be set to be more than 20mm and less than 30mm, for example.

[0065] The core 1 is preferably provided with a foam layer 2 on the outer peripheral surface. The foam layer 2 preferably has a 25% compression load of 10 kPa to 1000 kPa measured according to Japanese Industrial Standards (JIS) K 6254. By setting it to the above range, the yield of the adhesive sheet roll can be improved and the productivity can be improved. Furthermore, the deformation of the adhesive layer can be more effectively suppressed. A more preferred range is 30 kPa to 300 kPa, and a further preferred range is 50 kPa to 200 kPa.

[0066] The productivity of the double-sided adhesive sheet can be improved by aging in a roll state. On the other hand, if the double-sided adhesive sheet is aged in a roll state, the thickness deviation of the adhesive sheet becomes larger. One of the reasons is that during the aging process, the release sheet produces unevenness due to heat shrinkage.

[0067] The inventors of the present invention have repeatedly conducted diligent research, and the results show that by setting the standard deviation σ of the thickness Tt of the adhesive sheet to less than 10% of the layer thickness of the adhesive sheet, the generation of dents can be significantly suppressed. When the standard deviation σ of the thickness Tt of the adhesive sheet is less than 10% of the layer thickness of the adhesive sheet, the thickness deviation of the adhesive layer is small, so the close contact area between the adhesive layer and the release sheet becomes larger. It can be considered that the closely attached adhesive layer follows the unevenness caused by heat shrinkage of the release sheet during the aging process, preventing the dents of the adhesive sheet. On the other hand, when it is greater than 10%, the close contact between the adhesive layer and the release sheet decreases, so it is considered that when the adhesive layer follows the unevenness of the release sheet, tiny peeling occurs, resulting in the generation of dents. The standard deviation σ is more preferably less than 8%, and further preferably less than 5%.

[0068] As a method for setting the standard deviation σ of the thickness Tt of the adhesive sheet to 10% or less, there can be cited a method in which the light release sheet and the heavy release sheet are placed on the outside of the roll of an adhesive sheet roll in which the thickness and release force of each of the light release sheet and the heavy release sheet determined in the adhesive sheet are combined. In addition, there are a method of adjusting the thickness of the adhesive layer determined in the adhesive sheet, a method of adjusting the thickness of each of the light release sheet and the heavy release sheet determined in the adhesive sheet, etc.

[0069] 2. Adhesive layer

[0070] The adhesive layer is a double-sided adhesive layer with a thickness of 5 μm to 150 μm, and plays the role of bonding the adherends to each other. The adhesive layer is sandwiched by a light peeling sheet and a heavy peeling sheet at the stage of the adhesive sheet roller. The thickness Ta of the adhesive layer is more preferably in the range of 8 μm to 100 μm, and further preferably in the range of 25 μm to 75 μm. In addition, the thickness Ta of the adhesive layer can be obtained by the method of the embodiment described later.

[0071] From the viewpoint of resisting repeated bending, exhibiting excellent restoring force when returning to the original state from the bent state, and more effectively preventing deformation of the adhesive layer in the state of the adhesive sheet roll, the storage elastic modulus of the adhesive layer at a frequency of 1 Hz at 23°C is preferably 1×10 4 Pa~100×10 4 Pa. In addition, by using the adhesive layer in the above range, it is easy to design the balance of the peeling force with the light peeling sheet and the heavy peeling sheet. 4Pa or more, there is adhesion to the adherend, and it is easy to adjust the peeling force of the (ii) and (iii). In addition, the bending property of the adhesive layer can be excellent. The storage elastic modulus can be measured by the DHR-2 manufactured by TA Instruments (TA Instruments) company. The storage elastic modulus can be adjusted by the molecular weight of the monomer composition, the hardener, the drying conditions, etc. By being set to the scope, flexibility becomes good.

[0072] The adhesive force of the adhesive layer is preferably 10N / 25mm~40N / 25mm relative to the polyimide substrate at 25°C. By setting it to the range, it is easy to adjust the peeling force with the light peel sheet and the heavy peel sheet to the range. In addition, flexibility can be effectively exerted. A more preferred range is 15N / 25mm~35N / 25mm, and a further preferred range is 20N / 25mm~30N / 25mm. The adhesive force of the adhesive layer can be controlled by the composition of the adhesive resin constituting the adhesive composition described later, the Tg of the adhesive resin, the amount of the hardener in the adhesive composition, etc. In the case of using an acrylic copolymer as the adhesive resin, the adhesive force can be increased by including a highly polar acrylic monomer derived from a carboxyl-containing monomer such as acrylic acid. In addition, the lower the Tg of the adhesive resin, the higher the tendency of the adhesive force. Furthermore, the less the amount of the hardener in the adhesive composition, the higher the tendency of the adhesive force.

[0073] The adhesive layer 7 is a layer formed of an adhesive composition. The adhesive composition is a cross-linked adhesive or a non-cross-linked adhesive, and may be any of an emulsion type, a solvent type, and a solvent-free type.

[0074] The adhesive composition contains an adhesive resin as a main component. In addition, the so-called main component mentioned here refers to the component with the largest content (mass) in the non-volatile component. Adhesive resins can be exemplified by acrylic copolymers, rubber resins, silicone resins, urethane resins, polyamide resins, polyimide resins, polyester resins, and fluororesins. These resins can be used alone or in combination of two or more. From the perspective of excellent transparency on the basis of adhesion, acrylic copolymers are suitable.

[0075] This adhesive composition may include a hardener as required. As a hardener, for example, isocyanate compounds, epoxy compounds, aziridine compounds, carbodiimide compounds, metal chelates, etc. can be listed. The hardener can be a low molecular compound or a polymer compound. Among these, isocyanate compounds are preferably used in terms of the viewpoint of being able to take into account both high cohesion and close adhesion.

[0076] As a suitable adhesive layer, there can be mentioned an adhesive layer obtained by crosslinking an adhesive composition containing a (meth)acrylic acid copolymer, which has a gel fraction of 50% to 90% and a storage elastic modulus of 10 MPa or less at -30°C. As a suitable example of a (meth)acrylic acid copolymer, there can be mentioned a (meth)acrylic acid copolymer (a) having a structural unit derived from an alicyclic (meth)acrylate monomer and / or a structural unit derived from a linear or branched alkyl (meth)acrylate monomer having an alkyl group with 8 to 20 carbon atoms.

[0077] As further suitable examples of the (meth)acrylic copolymer (a), there can be mentioned a (meth)acrylic copolymer (a) having a structural unit derived from an alicyclic (meth)acrylate monomer and / or a structural unit derived from a linear alkyl (meth)acrylate monomer having an alkyl group with 10 to 20 carbon atoms, and a structural unit derived from a branched alkyl (meth)acrylate monomer having 8 to 20 carbon atoms.

[0078] By including a structural unit derived from an alicyclic (meth)acrylate monomer and / or a structural unit derived from a linear alkyl (meth)acrylate monomer having an alkyl group with 10 to 20 carbon atoms, the stress applied when the adhesive layer is repeatedly bent can be alleviated, and the deviation of the adhesive layer can be prevented. In addition, by including a structural unit derived from a branched alkyl (meth)acrylate monomer having 8 to 20 carbon atoms, the cohesive force of the adhesive layer is improved, whitening of the bent portion can be prevented, and the evaluation of bubbles described in the examples becomes good.

[0079] The more suitable range of the gel fraction is 55% to 85%, and the further suitable range is 60% to 80%. In addition, the more preferred range of the storage elastic modulus of the adhesive layer at -30°C is 8 MPa or less, and the further preferred range is 5 MPa or less. By setting the gel fraction to the above range, the bubbles in the bending part are improved.

[0080] The gel fraction of the adhesive layer can be adjusted according to the aging time, the adjustment of the aging temperature, and the amount of the hardener. In the (meth)acrylic copolymer (a), the gel fraction can be controlled within the range by adjusting the proportion of the hydroxyl-containing monomer. By increasing the proportion of the hydroxyl-containing monomer, the gel fraction tends to be higher. From the viewpoint of bubbles in the bending part, the lower limit of the storage elastic modulus of the adhesive layer at -30°C is preferably set to 0.5MPa. The storage elastic modulus can be adjusted by using structural units derived from linear and / or branched alkyl (meth)acrylate monomers having 8 to 20 carbon atoms in the alkyl group in the (meth)acrylic copolymer (a). The more carbon atoms in the alkyl (meth)acrylate monomer, or the more branched parts, the larger the volume of the alkyl group is entangled with each other in the adhesive layer, so the storage elastic modulus tends to be lower.

[0081] 2-1. Adhesive resin

[0082] From the perspective of both strength and stamping workability, the weight average molecular weight (Mw) of the adhesive resin is 500,000 or more, preferably 800,000 to 1.8 million, more preferably 900,000 to 1.7 million, and even more preferably 1 million to 1.5 million. In addition, with respect to the Tg of the adhesive resin, from the perspective of making the softness of the adhesive layer excellent, the value obtained by differential scanning calorimetry (DSC) of the adhesive layer is preferably below -30°C, more preferably below -32°C, and even more preferably below -35°C. The lower limit of the Tg of the adhesive resin is not particularly limited, but from the perspective of heat resistance, it is preferably above -50°C.

[0083] The (meth)acrylic acid copolymer is obtained by copolymerizing, for example, a functional group-containing monomer and a (meth)acrylic acid ester. As a suitable example of the (meth)acrylic acid ester, an alkyl (meth)acrylate can be mentioned.

[0084] The alkyl group of the (meth)acrylic acid alkyl ester may be any of a linear alkyl group, a branched alkyl group or a cyclic alkyl group. The alkyl group is preferably an alkyl group having 1 to 20 carbon atoms. From the viewpoint of improving the bendability, it is preferred to copolymerize monomers of a linear or branched alkyl (meth)acrylic acid ester monomer containing at least a cyclic alkyl group (alicyclic) and / or an alkyl group having 8 to 20 carbon atoms. Specific examples of the monomers include: methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate , isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, 4-n-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate. Among these, methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-butyl (meth)acrylate, hexyl (meth)acrylate, dodecyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate are preferred, and 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate are particularly preferred.

[0085] The alkyl (meth)acrylate preferably has a homopolymer Tg of -80°C to 110°C. It is also preferred to use an alkyl (meth)acrylate having a linear alkyl group and an alkyl (meth)acrylate having an alicyclic alkyl group in combination.

[0086] The Tg of the homopolymer can be calculated from the Tgn of a polymer obtained by polymerizing an alkyl (meth)acrylate alone according to the following Fox equation.

[0087] Fox formula: 100 / Tg = Σ(Wn / Tgn)

[0088] Tg: Calculated Tg of polymer (K)

[0089] Wn: mass fraction of monomer n (%)

[0090] Tgn: glass transition temperature of the homopolymer of monomer n (K)

[0091] The Tg value (Tgn) of the homopolymer of monomer n is described in, for example, technical data of monomer manufacturers such as Nippon Catalyst Co., Ltd., Mitsubishi Chemical Co., Ltd., and Toagosei Co., Ltd., or in the Polymer Data Handbook (published by Peifukan, edited by the Polymer Society (Basic Edition), first edition in January 1986), and the fourth edition of the Polymer Handbook (J. Brandrup, EH Immergut, EA Grulke, published in 1999, Wiley-Interscience). For example, the Tg of the homopolymer of each monomer is methyl methacrylate (105° C.), dodecyl acrylate (−10° C.), 2-ethylhexyl acrylate (−70° C.), butyl acrylate (−54° C.), isobornyl acrylate (94° C.), cyclohexyl acrylate (19° C.), and 4-hydroxybutyl acrylate (−40° C.).

[0092] Among the (meth)acrylic acid copolymers, the (meth)acrylic acid copolymer (a) is particularly preferred. The structural unit derived from a linear or branched (meth)acrylic acid alkyl ester having an alkyl group with 8 to 20 carbon atoms is preferably 10 to 100% by mass, more preferably 20 to 90% by mass, and even more preferably 30 to 85% by mass, relative to 100% by mass of the (meth)acrylic acid copolymer (a).

[0093] Furthermore, the amount of the structural unit derived from an alicyclic (meth)acrylate monomer and / or the structural unit derived from a linear alkyl (meth)acrylate monomer having an alkyl group with 10 to 20 carbon atoms is preferably 10 to 90% by mass, more preferably 10 to 75% by mass, and still more preferably 15 to 50% by mass, based on 100% by mass of the (meth)acrylic copolymer (a).

[0094] The content of the structural unit derived from a branched alkyl (meth)acrylate monomer having 8 to 20 carbon atoms is preferably 10 to 90% by mass, more preferably 20 to 85% by mass, and even more preferably 40 to 85% by mass, based on 100% by mass of the (meth)acrylic copolymer (a).

[0095] The (meth)acrylic acid copolymer (a) may contain a monomer containing a functional group. Examples of the monomer containing a functional group include a carboxyl group-containing monomer, a hydroxyl group-containing monomer, an epoxy group-containing monomer, and an amino group-containing monomer. By containing a monomer containing a functional group, the cohesive force of the adhesive is improved, and a strong adhesive layer can be obtained.

[0096] Examples of carboxyl group-containing monomers include (meth)acrylic acid, β-carboxyethyl acrylate, p-carboxybenzyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, citraconic acid, and isocrotonic acid. Among these, (meth)acrylic acid is particularly preferred from the viewpoint of cohesive force and adhesive force.

[0097] Examples of hydroxyl-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. Among these, 4-hydroxybutyl (meth)acrylate and 2-hydroxyethyl (meth)acrylate are more preferred from the viewpoint of cohesive force and adhesive force.

[0098] Examples of the epoxy group-containing monomer include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and 6-methyl-3,4-epoxycyclohexylmethyl (meth)acrylate.

[0099] Examples of the amino group-containing monomer include monoalkylamino (meth)acrylates such as monomethylaminoethyl (meth)acrylate, monoethylaminoethyl (meth)acrylate, monomethylaminopropyl (meth)acrylate, and monoethylaminopropyl (meth)acrylate.

[0100] The total amount of the structural units derived from the functional group-containing monomer is preferably 1 to 20% by mass relative to 100% by mass of the (meth)acrylic copolymer (a). By setting the content within the above range, the cohesive force can be adjusted by reaction with the curing agent, and the flexibility and restoring force can be improved.

[0101] Relative to 100% by mass of the (meth) acrylic copolymer (a), the structural unit derived from the monomer containing a carboxyl group is preferably 1% to 10% by mass. By being within the range, the cohesive force and the relaxation of the adhesive layer can be taken into account. In addition, relative to 100% by mass of the (meth) acrylic copolymer (a), the structural unit derived from the monomer containing a hydroxyl group is preferably 1% to 10% by mass. By being within the range, the adhesion and the relaxation of the adhesive layer can be taken into account.

[0102] The (meth)acrylic acid copolymer (a) may contain structural units derived from other monomers that can be copolymerized with the monomer. For example, monomers having an alkylene oxide group and other vinyl monomers can be cited. For example, methoxyethyl acrylate, methoxydiethylene glycol acrylate, vinyl acetate, vinyl crotonate, styrene, and acrylonitrile can be illustrated. In 100% by mass of the (meth)acrylic acid copolymer (a), the structural units derived from other monomers are preferably 0.1% by mass to 20% by mass.

[0103] The (meth)acrylic acid copolymer (a) is obtained by polymerizing a monomer mixture. During the polymerization, a polymerization initiator can be used as needed. The content of the polymerization initiator is, for example, 0.01 to 10 parts by mass relative to 100 parts by mass of the monomer mixture. The polymerization method is not limited. For example, solution polymerization, block polymerization, emulsion polymerization, and suspension polymerization can be exemplified. The solvent used in the solution polymerization can be exemplified by acetone, methyl acetate, ethyl acetate, toluene, xylene, anisole, methyl ethyl ketone, and cyclohexanone. The polymerization temperature is, for example, 60°C to 120°C, and the polymerization time is about 5 to 12 hours.

[0104] The polymerization initiator is preferably a free radical polymerization initiator. As the free radical polymerization initiator, peroxides and azo compounds are suitable. Examples of azo compounds include: 2,2'-azobisisobutyronitrile (abbreviation: AIBN (2,2'-azobisisobutyronitrile)), 2,2'-azobis(2-methylbutyronitrile) and other 2,2'-azobisbutyronitrile; 2,2'-azobisvaleronitrile such as 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile); 2,2'-azobispropionitrile such as 2,2'-azobis(2-hydroxymethylpropionitrile); 1,1'-azobis-1-alkanenitrile such as 1,1'-azobis(cyclohexane-1-carbonitrile). Examples of peroxides include dialkyl peroxides such as di-tert-butyl peroxide, diisopropyl peroxide, tert-butyl isopropyl peroxide, α,α'-bis(tert-butylperoxy-m-isopropyl)benzene, and 2,5-di(tert-butylperoxy)hexyne-3-ol; peroxyesters such as tert-butyl peroxybenzoate, tert-butyl peroxyacetate, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane; ketone peroxides such as cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, and methylcyclohexanone peroxide; 2,2-bis(4,4-di-tert-butylperoxycyclohexanone); Peroxy ketals such as 1,1-bis(tert-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, and n-butyl-4,4-bis(tert-butylperoxy)valerate; hydroperoxides such as isopropylbenzene hydroperoxide, diisopropylbenzene hydroperoxide, and 2,5-dimethylcyclohexane-2,5-dihydroperoxide; diacyl peroxides such as benzoyl peroxide, decanoyl peroxide, lauroyl peroxide, and 2,4-dichlorobenzoyl peroxide; peroxy dicarbonates such as bis(tert-butylcyclohexyl) peroxy dicarbonate.

[0105] 2-2. Hardener

[0106] This adhesive composition may contain a hardener as required. By having a cross-linked structure, an adhesive layer with excellent adhesion and cohesion can be provided. The suitable example of the hardener can be designed according to the functional group of the adhesive resin. As suitable hardeners, isocyanate compounds, epoxy compounds, aziridine compounds, carbodiimide compounds or metal chelates, etc. can be listed. When the functional group is a hydroxyl group or a carboxyl group, isocyanate compounds and epoxy compounds are preferably used. Among these, isocyanate compounds are preferably used in terms of the viewpoint of being able to take into account both high cohesion and close adhesion. As a suitable example, an adhesive composition with (methyl) acrylic copolymer (a) as an adhesive resin and an isocyanate compound as a hardener can be listed.

[0107] The isocyanate compound is an isocyanate having two or more isocyanate groups and is preferably an isocyanate monomer such as aromatic polyisocyanate, aliphatic polyisocyanate, aromatic aliphatic polyisocyanate, alicyclic polyisocyanate, and a biuret form, urate form, and adduct thereof.

[0108] Examples of the aromatic polyisocyanate include 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanatotoluene, 1,3,5-triisocyanatobenzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate.

[0109] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HMDI (hexamethylene diisocyanate)), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0110] Examples of the aromatic aliphatic polyisocyanate include ω,ω′-diisocyanate-1,3-dimethylbenzene, ω,ω′-diisocyanate-1,4-dimethylbenzene, ω,ω′-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.

[0111] Examples of the alicyclic polyisocyanate include 3-isocyanate methyl-3,5,5-trimethylcyclohexyl isocyanate (also known as IPDI (isophorone diisocyanate), isophorone diisocyanate), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4′-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanate methyl)cyclohexane.

[0112] The biuret form is a self-condensation product having a biuret bond formed by self-condensation of an isocyanate monomer. Examples of the biuret form include a biuret form of hexamethylene diisocyanate.

[0113] The urate body is a trimer of an isocyanate monomer, and examples thereof include a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate, and a trimer of toluene diisocyanate.

[0114] The adduct is a difunctional or higher isocyanate compound formed by reacting an isocyanate monomer with a difunctional or higher compound containing low molecular active hydrogen. Examples of the adduct include a compound formed by reacting trimethylolpropane with hexamethylene diisocyanate, a compound formed by reacting trimethylolpropane with toluene diisocyanate, a compound formed by reacting trimethylolpropane with xylylene diisocyanate, a compound formed by reacting trimethylolpropane with isophorone diisocyanate, and a compound formed by reacting 1,6-hexanediol with hexamethylene diisocyanate.

[0115] From the viewpoint of forming a sufficient cross-linked structure, the isocyanate compound is preferably a trifunctional isocyanate compound. The isocyanate compound is more preferably an adduct of a reaction product of an isocyanate monomer and a trifunctional compound containing low molecular active hydrogen, and a urate body. The isocyanate compound is preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a urate body of hexamethylene diisocyanate, a trimethylolpropane adduct of toluene diisocyanate, a urate body of toluene diisocyanate, a trimethylolpropane adduct of isophorone diisocyanate, and a urate body of isophorone diisocyanate, more preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of toluene diisocyanate, and a trimethylolpropane adduct of isophorone diisocyanate.

[0116] Examples of the epoxy compound include glycerol diglycidyl ether, 1,6-hexanediol diglycidyl ether, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidylaminophenylmethane.

[0117] Examples of the aziridine compound include N,N′-diphenylmethane-4,4′-bis(1-aziridinecarboxamide), tris-2,4,6-(1-aziridinyl)-1,3,5-triazine, and 4,4′-bis(ethyleneiminocarbonylamino)diphenylmethane.

[0118] The carbodiimide compound is preferably a high molecular weight polycarbodiimide generated by subjecting a diisocyanate compound to a decarbonation condensation reaction in the presence of a carbodiimidization catalyst. The commercially available product of the high molecular weight polycarbodiimide is preferably the Carbodilite series of Nissinbo Co., Ltd. Among them, Carbodilite V-03, 07, and 09 are preferably preferred due to their excellent compatibility with organic solvents.

[0119] The metal chelate is preferably a coordination compound of a polyvalent metal such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium with acetylacetone or ethyl acetylacetate. Examples of the metal chelate include ethyl acetylacetate aluminum-diisopropyl alcohol ester, aluminum triacetylacetonate, bisethyl acetylacetate aluminum-monoacetylacetonate, and alkyl acetylacetate aluminum-diisopropyl alcohol ester.

[0120] The hardener is preferably contained in an amount of 0.001 to 1 part by mass, more preferably 0.01 to 0.1 part by mass, relative to 100 parts by mass of the adhesive resin. If the content is 0.01 parts by mass or more, the cohesive force is further improved, and if the content is 1 part by mass or less, it is easy to achieve both cohesive force and flexibility, so it is preferred.

[0121] 2-3. Other additives

[0122] The adhesive composition may further contain a solvent, a tackifier, a silane coupling agent, a filler, a tackifier resin, a colorant, an antioxidant, an antistatic agent, an ultraviolet absorber, etc. as necessary.

[0123] Examples of the solvent include esters such as ethyl acetate, propyl acetate, and butyl acetate; and ketones such as acetone, methyl ethyl ketone, and cyclohexanone. In addition, examples include aromatic hydrocarbons such as toluene, xylene, benzene, and solvent naphtha; and aliphatic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, ethylcyclohexane, diethylcyclohexane, decahydronaphthalene, bicycloheptane, tricyclodecane, hexahydroindenylcyclohexane, cyclooctane, α-pinene, terpinolene, and limonene. The solvent may be used alone or in combination.

[0124] Examples of the silane coupling agent include alkoxysilane compounds having a (meth)acryloxy group such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropyltripropoxysilane, 3-(meth)acryloxypropyltributoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane;

[0125] Alkoxysilane compounds having a vinyl group, such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, vinyltributoxysilane, vinylmethyldimethoxysilane, and vinylmethyldiethoxysilane;

[0126] Alkoxysilane compounds having an amino group such as 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltripropoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane;

[0127] Alkoxysilane compounds having a mercapto group such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltripropoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropylmethyldiethoxysilane;

[0128] Alkoxysilane compounds having an epoxy group, such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyltripropoxysilane, 3-glycidoxypropyltributoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane;

[0129] Tetraalkoxysilane compounds such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane;

[0130] 3-Chloropropyltrimethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, n-decyltrimethoxysilane, n-decyltriethoxysilane, styryltrimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, hexamethyldisilazane, silicone resin having an alkoxysilyl group in the molecule, and the like.

[0131] The silane coupling agent is used in an amount of preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, based on 100 parts by mass of the adhesive resin.

[0132] By adding a filler, optical and mechanical properties can be adjusted. Examples of the filler include inorganic white pigments such as silicon dioxide, calcium carbonate, aluminum hydroxide, magnesium hydroxide, clay, talc, and titanium dioxide.

[0133] Adhesion imparting resins include, for example, rosin resins, polymerized rosin resins, rosin ester resins, polymerized rosin ester resins, terpene resins, terpene phenol resins, coumarone resins, coumarone indene resins, xylene resins, phenol resins, petroleum resins, etc. In the case of using acrylic copolymers as adhesive resins, in terms of good compatibility and further improved adhesion performance, rosin resins, polymerized rosin resins, rosin ester resins and polymerized rosin ester resins are preferred, and rosin ester resins and polymerized rosin ester resins are more preferred. Relative to 100 parts by mass of (meth) acrylic copolymer (a), adhesion imparting resins are preferably used in an amount of 0.01 to 10 parts by mass, more preferably 0.5 to 7 parts by mass. If 0.01 to 10 parts by mass of adhesion imparting resins are used, high adhesion can be obtained.

[0134] 3. Light peeling sheet and heavy peeling sheet

[0135] The light release sheet and the heavy release sheet play the role of protecting the adhesive layer. The light release sheet and the heavy release sheet use sheets that meet the above (ii) to (v). A more suitable range of Tl is 25μm to 75μm, and a further suitable range is 25μm to 50μm. In addition, a more suitable range of Th is 50μm to 150μm, and a further suitable range is 75μm to 125μm. From the perspective of improving productivity, the light release sheet and the heavy release sheet can also be made of the same material with different thicknesses.

[0136] The film thickness difference (Th-Tl) is preferably set to 15 μm or more, and more preferably set to 25 μm or more. The upper limit is preferably 140 μm or less, and more preferably 95 μm or less. By setting the film thickness difference to 15 μm or more, the stress applied to the adhesive during the peeling of the light peeling sheet can be dispersed to the heavy peeling sheet, thereby preventing the cohesion and destruction of the adhesive during peeling. By setting the film thickness difference to 140 μm or less, the stress applied to the adhesive during the peeling of the light peeling sheet can be dispersed to the heavy peeling sheet, making it easy and smooth to peel off the light peeling sheet, thereby preventing tearing.

[0137] The more suitable range of Ph / Pl is 2.5 to 5. In addition, the more suitable range of Pl is 0.02N / 25mm to 0.2N / 25mm, and the more suitable range is 0.02N / 25mm to 0.1N / 25mm. The more suitable range of Ph is 0.15N / 25mm to 0.6N / 25mm, and the more suitable range is 0.2N / 25mm to 0.5N / 25mm.

[0138] Examples of the light release sheet and the heavy release sheet (hereinafter, also collectively referred to as "release sheet") include polyethylene sheets, polypropylene sheets, polybutylene sheets, polybutadiene sheets, polymethylpentene sheets, polyvinyl chloride sheets, vinyl chloride copolymer sheets, polyethylene terephthalate sheets, polyethylene naphthalate sheets, polybutylene terephthalate sheets, polyurethane sheets, ethylene vinyl acetate sheets, ionomer resin sheets, ethylene-(meth)acrylic acid copolymer sheets, ethylene-(meth)acrylate copolymer sheets, polystyrene sheets, polycarbonate sheets, polyimide sheets, and fluororesin sheets. The release sheet may be a single layer or a laminate.

[0139] In addition to using a release sheet having release properties on the release sheet itself, a release sheet with a release agent applied to the substrate can also be used. By applying a release agent on the bonding surface with the adhesive layer, release properties can be imparted. In addition to having a substrate / release layer, the release sheet can also have other functional layers. As the release layer having other functional layers, antistatic layer / substrate / release layer, substrate / antistatic layer / release layer can be exemplified.

[0140] Specific examples of release agents include alkyd, silicone, fluorine, unsaturated polyester, polyolefin, and wax. (ii) to (iv) can be adjusted according to the type of release agent. As another method of adjusting (ii) to (iv), there is a method of adjusting the thickness of the light release sheet and the heavy release sheet as described above.

[0141] From the viewpoint of ease of designing the peel strength, silicone-based release agents are suitable. As a suitable example, a release agent having a linear silicone as a main component and further containing a branched silicone can be exemplified.

[0142] Silicone-based release agents include silicones having siloxane bonds on the main chain. As silicones, for example, various silicones with different peeling properties can be obtained by combining a type having three organic substituents bonded to silicon and one oxygen atom (M unit), a type having two organic substituents bonded to silicon and two oxygen atoms (D unit), a type having one organic substituent bonded to silicon and three oxygen atoms (T unit), and a type having no organic substituent bonded to silicon and four oxygen atoms (Q unit), and the ratio of these can be used to control the magnitude of the peeling strength. Most of them can be adjusted in the direction of reducing peeling by using straight-chain silicones containing M units and D units, and can be adjusted in the direction of increasing peeling by using branched silicones containing T units or Q units in the structure of straight-chain silicones.

[0143] The linear silicone preferably has D units as the main component and preferably has M units for adjusting the molecular weight. The organic substituent represents a hydrogen atom, a hydroxyl group or an alkyl group, and is preferably an alkyl group, specifically a methyl group or a phenyl group, from the viewpoint of being easily soluble in an organic solvent.

[0144] Straight-chain silicones can provide various resistances, so they can adopt a cross-linked structure. Straight-chain silicones preferably have two or more vinyl groups as cross-linking points at their ends and / or side chains. As hardeners, there are hydrogen-modified silicones, etc., and they need to have two or more SiH groups in one molecule. It is preferred to contain 0.1 to 20 parts by mass of hydrogen-modified silicone relative to 100 parts by mass of straight-chain silicone.

[0145] The branched silicone preferably has T units and / or Q units, and preferably contains 70% by mass or more of T units and / or Q units in 100% by mass of the branched silicone. In addition to T units and / or Q units, the branched silicone may have M units and D units.

[0146] The release layer is formed by a release agent. The release agent of the present invention contains linear silicone and branched silicone in a ratio of linear silicone: branched silicone = 100:0 to 99:1 (mass ratio). By setting it to contain 1% by mass or less of branched silicone relative to the total mass of the release agent (linear silicone, hydrogen-modified silicone and branched silicone), dustproofness or resistance to winding deviation is improved. The ratio of branched silicone is more preferably 0.5% by mass or less, and further preferably 0.2% by mass or less.

[0147] The total content of the linear silicone, hydrogen-modified silicone and branched silicone in 100 mass % of the total mass of the release agent is preferably 50 to 100 mass %, more preferably 80 to 100 mass %, and further preferably 90 to 100 mass %.

[0148] The silicone-based mold release agent can be synthesized by addition reaction, peroxide condensation reaction, and ultraviolet crosslinking reaction, but is preferably formed by addition reaction. The addition reaction is a crosslinking of the vinyl group contained in the linear silicone and the SiH group contained in the hydrogen-modified silicone.

[0149] In the case of synthesizing the release agent by addition reaction, a catalyst is included. The catalyst is not particularly limited, and is preferably a platinum catalyst, more preferably chloroplatinic acid, chloroplatinic acid, alcohol compounds of chloroplatinic acid, aldehyde compounds, or complexes of chloroplatinic acid and various olefins. In the total mass 100 mass % of the release agent, the amount of the catalyst added is preferably 0.01 mass % to 10 mass %, more preferably 0.2 mass % to 2 mass %.

[0150] The release agent may contain any appropriate other components within the range not impairing the effects of the present disclosure, such as reaction inhibitors, inorganic fillers, organic fillers, colorants (dyes or pigments, etc.), plasticizers, ultraviolet absorbers, antioxidants, etc.

[0151] The release layer is preferably formed by coating a release agent composition on a release substrate. The release agent may contain a solvent when applied. The type of solvent is not limited, and examples thereof include: hydrocarbon solvents such as n-hexane, cyclohexane, and n-heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and organic solvents such as alcohol solvents such as methanol, ethanol, and butanol.

[0152] The release agent can be applied to the substrate by a micro gravure coater, a gravure coater, or the like. The release agent can be applied to the substrate in a solid content mass of, for example, 0.1 g / m 2 ~2.0g / m 2 , preferably 0.5 g / m 2 ~1.2g / m 2 The coating is performed in a left-right manner, and a release layer is provided by curing.

[0153] The hardening of the coating film of the release agent is preferably thermal hardening. The addition reaction can be efficiently promoted by thermal hardening. The hardening temperature is not limited, and 80°C to 130°C is suitable. By setting it to above 80°C, the hardening reaction can be carried out efficiently, which can improve productivity. In addition, by setting it to below 130°C, the degradation of the substrate (wrinkles caused by heat, etc.) can be reduced, or the options for the substrate can be increased. The thickness of the release layer is not limited, for example, it is about 0.1μm to 2μm.

[0154] 4. Manufacturing of adhesive sheet roll

[0155] The adhesive sheet roll of the present disclosure can be manufactured by a known method. For example, an adhesive composition is applied to a heavy release sheet to form a coating film, which is hardened to form an adhesive layer, and a light release sheet is attached to one of the exposed surfaces of the adhesive layer to obtain an adhesive sheet. Then, the obtained adhesive sheet is rolled into a roll to obtain the adhesive sheet.

[0156] The coating can be carried out, for example, by a micro gravure coater, a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a rod coater, a rod blade coater, a knife coater, a spray coater, a die coater, or a curtain coater. In the case where the adhesive composition contains a solvent, after coating, the solvent is removed by a drying process. Hardening is hardened, for example, by aging. In the case of a light-curing adhesive composition, it is hardened by irradiating ultraviolet light (ultraviolet, UV) and the like.

[0157] After manufacturing the adhesive sheet, or while manufacturing the adhesive sheet, the adhesive sheet is wound in a roll shape on a reel, thereby obtaining an adhesive sheet roll. The length of the roll can be designed according to the purpose. In addition, although it can be designed appropriately according to the length of the adhesive sheet, from the perspective of improving productivity, it is preferably more than 50m, and more preferably more than 100m. From the perspective of manufacturing yield, the length of the roll is preferably set to less than 2500m.

[0158] Alternatively, the adhesive layer composition may be applied to the release surfaces of the light release sheet and the heavy release sheet so that the thickness after drying becomes a predetermined thickness to form two adhesive layers, and then the adhesive layers may be bonded.

[0159] 5. Flexible displays

[0160] The flexible display includes an optical element such as a liquid crystal element, an organic electroluminescence (EL) element, and an adhesive layer formed by an adhesive sheet rolled out from the adhesive sheet roll. A flexible display is a display that can be bent, preferably a display that can be repeatedly bent including bending. For example, an organic electroluminescence (organic EL) display, an electrophoretic display (electronic paper), a liquid crystal display using a plastic substrate (film) as a substrate, and a foldable display can be exemplified.

[0161] The adhesive layer formed by the adhesive sheet is suitable for bonding bendable components to each other, for example, it is suitable for bonding components of any combination of liquid crystal polymer sheets, light emitting polymer sheets, sheet-like liquid crystal modules, organic EL modules (organic EL sheets), electronic paper modules, transparent conductive sheets, metal mesh sheets, sheet sensors, cover sheets, barrier films, polarizing films, polarizers, phase difference films, viewing angle compensation films, brightness enhancement films, contrast enhancement films, diffusion films, semi-transmitting reflective films, and electrode films.

[0162] [Example 1]

[0163] Hereinafter, the present disclosure will be described in more detail based on the examples. However, the present disclosure is not limited thereto. Unless otherwise specified, the "parts" in the examples represent "parts by mass" and "%" represents "% by mass". Blank columns in the table represent that no blending is performed.

[0164] (a) Determination method

[0165] The numerical values ​​obtained in the present examples are values ​​obtained by the following method: Each measurement position (film thickness, peeling force, etc.) of the adhesive sheet roll was measured at a position of 50% of the winding length of the adhesive sheet roll.

[0166] a-1. Glass transition temperature

[0167] The glass transition temperature (Tg) of the (meth)acrylic acid copolymer (a) and the adhesive layer was measured using a robot DSC (differential scanning calorimeter, "RDC220" manufactured by Seiko Instruments). About 2 mg of the sample was placed in an aluminum pan, weighed, and placed in the differential scanning calorimeter, with an aluminum pan of the same type without the sample placed therein as a reference. After being kept at 100°C for 5 minutes, it was rapidly cooled to -120°C using liquid nitrogen, and then the temperature was raised at a rate of 5°C / min, and Tg (°C) was determined from the obtained DSC chart.

[0168] a-2. Mw of resin

[0169] Mw was determined by conversion using polystyrene having a known molecular weight as a standard substance using a gel permeation chromatograph (GPC) "LC-GPC system" manufactured by Shimadzu Corporation.

[0170] Device name: LC-GPC system "Prominence" manufactured by Shimadzu Corporation

[0171] Pipe string: Four GMHXL pipes manufactured by Tosoh and one HXL-H pipe manufactured by Tosoh are connected.

[0172] Mobile phase solvent: tetrahydrofuran

[0173] Flow rate: 1.0mL / min

[0174] Column temperature: 40℃

[0175] a-3. Film thickness

[0176] From the end of the width direction of the adhesive sheet roller to the other end, 10 positions at equal intervals are determined, and the thickness of the 10 positions is measured, and the average value is set as the thickness Tt of the adhesive sheet. In addition, the so-called end mentioned here refers to the end stacked with a light peeling sheet / adhesive layer / heavy peeling sheet. Then, the light peeling sheet is peeled off from the adhesive sheet roller, and the thickness of the light peeling sheet peeled off at 10 positions corresponding to the same position is measured. The average value is set as the thickness Tl of the light peeling sheet. Thereafter, the heavy peeling sheet is peeled off from the adhesive layer, and the thickness of the heavy peeling sheet peeled off at 10 positions corresponding to the same position is measured. The average value is set as the thickness Th of the heavy peeling sheet. The thickness Ta of the adhesive layer is obtained by Tt-Tl-Th.

[0177] a-4. Standard deviation of thickness of adhesive sheet

[0178] According to the above "a-3", the standard deviation σ of the thickness Tt of the adhesive sheet in the plane is determined. That is, the standard deviation σ is determined from the film thickness at 10 locations at equal intervals from one end to the other end in the width direction of the adhesive sheet roll.

[0179] a-5. Storage elastic modulus G' of adhesive layer (storage elastic modulus at -30°C)

[0180] Prepare two groups of adhesive sheets rolls with light release sheets peeled off, and use a laminator to bond the adhesive layers to each other to make a laminate of heavy release sheet / adhesive layer / heavy release sheet. The heavy release sheet on one side of the laminate is peeled off, and the adhesive sheet from which the light release sheet has been peeled off is repeatedly bonded to form a laminate of adhesive layers with a thickness of 1 mm. For the laminate, the storage elastic modulus G' is measured using a rheometer (manufactured by TA Instruments, DHR-2) with a measuring probe of φ8 mm under the conditions of strain 0.1%, frequency 1 Hz, and a heating rate of 10°C / min from -70°C to 200°C, and the storage elastic modulus G' at -30°C is obtained.

[0181] a-6. Peeling force Pl of the light release sheet relative to the adhesive layer

[0182] After the adhesive sheet is manufactured by the method described below, after 24 hours in an environment of 23° C. and a relative humidity of 50%, the light release sheet is peeled off at a peeling angle of 180° and a peeling speed of 300 mm / min in this environment to determine the peeling force Pl of the light release sheet relative to the adhesive layer.

[0183] a-7. Peel force Ph of heavy release sheet relative to adhesive layer

[0184] For the sample in a-6 in which the peeling force Pl of the light peeling sheet is determined, a 50 μm PET film (G2L, manufactured by Toyobo Co., Ltd.) is attached to the exposed surface of the adhesive layer, and then the heavy peeling sheet is peeled off at a peeling angle of 180° and a peeling speed of 300 mm / min to determine the peeling force Ph of the heavy peeling sheet relative to the adhesive layer.

[0185] a-8. Gel fraction of adhesive layer

[0186] The adhesive sheet was cut into a size of 30 mm × 100 mm, and the adhesive layer exposed after peeling off the light peel sheet was attached to a weighed 300-mesh stainless steel mesh (mass W0). Then, the heavy peel sheet was peeled off to obtain a sample of the stainless steel mesh / adhesive layer. The weighed mass of the sample was set as W1, and after the sample was left to stand in ethyl acetate for 24 hours, the sample was taken out and dried at 100°C for 1 hour. The weighed mass was set as W2, and calculated by the following formula.

[0187] Gel fraction (%) = {(W2-W0) / (W1-W0)}×100

[0188] (b) Production Example of Adhesive Resin

[0189] b-1. Adhesive resin R1

[0190] In a reaction container (hereinafter simply referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, a dropping device, and a nitrogen introduction tube, 100 parts of ethyl acetate, 83 parts of 2-ethylhexyl acrylate (2EHA), 15 parts of isobornyl acrylate (IBXA), 2 parts of 4-hydroxybutyl (meta) acrylate (4HAB), and 0.1 parts of 2,2'-azobisisobutyronitrile (hereinafter simply referred to as "AIBN") as an initiator were placed, and the atmosphere in the reaction container was replaced with nitrogen. Thereafter, the reaction solution was heated to 65°C while being stirred under a nitrogen atmosphere, and reacted at 65°C for 4 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an adhesive resin ((meth)acrylic acid copolymer (a)) R1 solution having a nonvolatile content of 30% (Mw: 1.2 million, Tg: -48°C).

[0191] b-2. Adhesive resin R2, adhesive resin R3

[0192] Adhesive resin ((meth)acrylic copolymer (a)) R2 and adhesive resin ((meth)acrylic copolymer (a)) R3 were obtained by the same method as adhesive resin R1 except that the monomers and the blending amounts were changed as shown in Table 1. Mw and Tg are shown in Table 1.

[0193] The symbols in Table 1 are as follows.

[0194] MA: Methyl acrylate (the carbon number of the linear alkyl group is 1)

[0195] BA: Butyl acrylate (straight chain alkyl with 4 carbon atoms)

[0196] 2EHA: 2-ethylhexyl acrylate (branched alkyl has 8 carbon atoms)

[0197] DOA: dodecyl acrylate (linear alkyl group has 12 carbon atoms)

[0198] IBXA: Isobornyl acrylate (alicyclic alkyl)

[0199] CHA: Cyclohexyl acrylate (alicyclic alkyl)

[0200] 4HBA: 4-Hydroxybutyl (meth)acrylate

[0201] AA: Acrylic acid

[0202] [Table 1]

[0203]

[0204] (c) Preparation of adhesive composition

[0205] c-1. Production of Adhesive Composition C1

[0206] 0.5 parts of aromatic isocyanate D-110N as a curing agent was added to 100 parts of nonvolatile components of the adhesive resin R1, and ethyl acetate was further added so that the nonvolatile content was 20%, and the mixture was stirred to obtain an adhesive composition C1 (see Table 2).

[0207] c-2. Production of Adhesive Compositions C2 and C3

[0208] Adhesive compositions C2 and C3 were obtained by the same method as that for the adhesive composition C1 except that the adhesive resin R1 was changed to the adhesive resin R2 and the adhesive resin R3 (see Table 2).

[0209] [Table 2]

[0210]

[0211] (d) Production of release sheet

[0212] d-1. Peel sheet RS1

[0213] 100 parts of silicone A, 1 part of platinum catalyst, and 200 parts of toluene are prepared, and the mixture is thoroughly mixed and stirred to prepare a release agent. The obtained release agent is applied to a polyethylene terephthalate (PET) film having a film thickness of 49 μm by a gravure coater in a manner that the film thickness after drying becomes 1 μm, and dried at 120°C for 2 minutes to obtain a 50 μm release sheet RS1 having a release layer. On the release layer of the release sheet RS1, an adhesive composition C1 is applied in a manner that the thickness Ta after drying becomes 50 μm. After coating, it is dried at 100°C for 3 minutes to form an adhesive layer. Subsequently, a PET film of 50 μm (G2L, manufactured by Toyobo Co., Ltd.) is bonded to the exposed surface of the adhesive layer to obtain a test piece having a structure of release sheet RS1 / adhesive layer L1 / PET film. Then, the peeling force was determined when the release sheet RS1 was peeled off from the adhesive layer at a peeling angle of 180° and a peeling speed of 300 mm / min under an environment of 23° C. and a relative humidity of 50%.

[0214] d-2. Peeling sheet RS2 to peeling sheet RS24

[0215] Release sheets RS2 to RS24 were obtained by the same method as release sheet RS1, except that the formulation components of the release agent, the thickness of the release agent after drying on the substrate, the type and thickness of the substrate were changed as shown in Table 3. In addition, the release force of each release sheet with respect to the adhesive layer L1 was also shown in Table 3 by the same method as release sheet RS1.

[0216] The symbols in Table 3 are as follows.

[0217] Silicone A: KS-847 (manufactured by Shin-Etsu Silicone Co., Ltd.)

[0218] Silicone B: DOWSIL (registered trademark) LTC755 coating (manufactured by Dow-Toray)

[0219] Silicone C: KS-841 (manufactured by Shin-Etsu Silicone Co., Ltd.)

[0220] Silicone D: KS-830E (manufactured by Shin-Etsu Silicone Co., Ltd.)

[0221] Silicone E: DOWSIL LTC 759 coating (manufactured by Dow-Toray)

[0222] Platinum catalyst: Platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution (manufactured by Sigma Aldrich)

[0223]

[0224] (e) Example of manufacturing adhesive sheet roll

[0225] e-1. Example 1

[0226] When manufacturing the adhesive sheet roller, a coating machine including a heavy release sheet supply unit, a die coating machine head, a drying furnace, a light release sheet and a laminating machine is used. First, a heavy release sheet roller (release sheet RS3, size width 1100mm×100m) is set in the heavy release sheet supply unit, and the adhesive composition C1 is applied to the release layer of the heavy release sheet in such a way that the thickness Ta after drying becomes 25μm. After coating, it is dried at 100°C for 3 minutes to form an adhesive layer. The coating layer is provided with a 25mm non-adhesive layer forming portion at both ends of the heavy release sheet in the width direction.

[0227] Then, a light release sheet roll (release sheet RS11, size width 1100mm × length 100m) is set in the light release sheet supply part, and the demoulding layer of the light release sheet is attached to the exposed surface of the adhesive layer to obtain an adhesive sheet S1 having a structure of "heavy release sheet / adhesive layer / light release sheet". Thereafter, the adhesive sheet S1 is wound on a core with a diameter of 3 inches and a length of 120cm, and then aged for 1 week at a temperature of 25°C and a relative humidity of 50%, thereby obtaining an adhesive sheet roll having an adhesive layer of 1.1m in width and 100m in length. The film thickness, peeling force, etc. are measured at 50% of the length of the adhesive sheet roll (the position where 50m is rolled out).

[0228] e-2. Examples 2 to 26, Comparative Examples 1 to 8

[0229] The adhesive sheet rolls of the respective examples and comparative examples were obtained by the same method as in Example 1 except that the types of the adhesive composition, the light release sheet, and the heavy release sheet were changed as shown in Tables 4 to 6.

[0230] (g) Evaluation of adhesive sheet roll

[0231] g-1. Observation of dents

[0232] The adhesive sheet roll of each embodiment and comparative example was rolled out, and a light source (230VILS, manufactured by USHIO Electric Co., Ltd.) was irradiated to the adhesive sheet from the front at a distance of 100 cm, and the adhesive sheet was projected at the same magnification onto a screen located 100 cm behind. Then, the screen was visually observed and the dents of the adhesive sheet were evaluated according to the following criteria. In addition, the dent refers to the dent that can be counted by visual observation, and the dent with a major diameter of 0.5 mm or more is counted as 1.

[0233] 5: less than 50 dents / m 2 .

[0234] 4: 50 dents / m 2 More than but less than 100 pieces / m 2 .

[0235] 3: 100 dents / m 2 More than but less than 300 pieces / m 2 .

[0236] 2: 300 dents / m 2 More than but less than 500 pieces / m 2 .

[0237] 1: 500 dents / m 2 More than but less than 1000 pieces / m 2 .

[0238] g-2. Bubbles during folding

[0239] The adhesive sheet roll of each example and comparative example was unwound, the light release sheet was peeled off, and the exposed adhesive layer was laminated on the polyimide film.

[0240] Then, the heavy release sheet was peeled off from the adhesive layer, and the exposed adhesive layer was laminated on the easy-bonding PET film. The laminate was put into an autoclave and kept at 50° C. for 20 minutes. Then, the laminate was taken out and left to stand at 23° C. and 50% RH for 30 minutes, and then cut into a size of 70 mm in width and 100 mm in length to obtain a test laminate including easy-bonding PET film / adhesive layer / polyimide.

[0241] Then, at 25°C and 50% RH, the test laminate was twisted to the left and right using a planar body unloaded torsion tester (manufactured by Yuasa System Machine Co., Ltd.), and then restored to the state before the twisting, and the same operation was performed for 200,000 cycles as one cycle. The number of sample tests was N = 5, and the appearance after the test was evaluated visually. The evaluation criteria are as follows. In addition, the bubbles were visually judged, and the bubbles with a diameter of more than 100 μm were counted.

[0242] 5: No bubbles were observed in all 5 samples.

[0243] 4: Bubbles were visible in 1 sample.

[0244] 3: Bubbles were visible in 2 samples.

[0245] 2: Bubbles were visible in 3 samples.

[0246] 1: Bubbles are visible in 4 samples or in all samples.

[0247] g-3. Stamping yield

[0248] The sheet was punched out using a die (Thomson knife). The punched shape and size were set to A4. The processing yield was set to the frequency at which no forced separation occurred when the punching process was performed 20 times.

[0249] 5: The number of times that forced separation occurs is 1 or less.

[0250] 4: The number of times that forced separation occurs is 2 or more and 3 or less.

[0251] 3: The number of times that forced separation occurs is 4 or more and 5 or less.

[0252] 2: The number of times that forced separation occurs is 6 or more and 7 or less.

[0253] 1: The number of times of forced separation occurs is 8 or more.

[0254] g-4. Deformation of adhesive layer after lamination

[0255] The light peeling sheet was peeled off from the adhesive sheet, and a PET film 50μm (G2L, manufactured by Toyobo Co., Ltd.) was attached as the adherend to make a test piece with a width of 1000mm×length of 1000mm. A light source (230VILS, manufactured by USHIO Electric Co., Ltd.) was irradiated to the test piece from the front at a distance of 100cm, and the test piece was directly observed visually from a distance of less than 20cm, and the floating of the adhesive layer was evaluated according to the following benchmarks. In addition, floating refers to floating of more than 0.5mm. In addition, in the case of a large floating of more than 10mm, the evaluation is set to 1.

[0256] 5: Less than 10 pieces / m with a float less than 1 mm 2 , the floating of 1mm or more and less than 10mm is less than 10 pieces / m 2 .

[0257] 4: Less than 30 pieces / m with a float less than 1 mm 2 , the floating of 1mm or more and less than 10mm is less than 10 pieces / m 2 .

[0258] 3: Less than 30 pieces / m with a float less than 1 mm 2 , 10 pieces / m for floatation of 1mm or more and less than 10mm 2 above.

[0259] 2: 30 pieces / m for floats less than 1 mm 2 Above, the floating of 1mm and less than 10mm is less than 10 pieces / m 2 .

[0260] 1: None of the above evaluations 2 to 5 are met. Or the number of floating of 10 mm or more is 1 piece / m 2 above.

[0261] [Table 4]

[0262]

[0263] [Table 5]

[0264]

[0265] [Table 6]

[0266]

[0267] Regarding the adhesive sheet roll in which the heavy release sheet is rolled out, as shown in Comparative Example 1, problems were confirmed in the bubbles and deformation of the adhesive layer after bonding. In addition, regarding the adhesive sheet roll formed by the release sheet whose release force Pl is outside the range of 0.02N / 25mm~0.30N / 25mm even if the release force ratio Ph / Pl satisfies 2~6, or the release force Ph is outside the range of 0.10N / 25mm~0.80N / 25mm, as shown in Comparative Examples 2 and 3, it was confirmed that there was a problem with the generation of bubbles. Similarly, regarding the adhesive sheet roll in which the release sheet whose release force ratio Ph / Pl does not satisfy 2~6 is combined, as shown in Comparative Examples 4, 5, and 7, it was confirmed that there was a problem with the generation of bubbles. Regarding the adhesive sheet roll having an adhesive layer with a thickness of more than 150μm, as shown in Comparative Example 6, the generation of dents was confirmed. In addition, regarding the adhesive sheet roll in which the light release sheet and the heavy release sheet are combined with release sheets of the same thickness or Tl>Th, there is a problem in the generation of dents as shown in Comparative Examples 7 and 8. On the other hand, according to this embodiment, it is confirmed that a high-quality adhesive sheet roll can be provided which suppresses the generation of dents and bubbles, has an excellent punching yield, and can also suppress the deformation of the adhesive layer after bonding.

Claims

1. An adhesive sheet roll for a flexible display, wherein a long adhesive sheet is wound on a core, wherein: The adhesive sheet has an adhesive layer sandwiched by a light release sheet and a heavy release sheet and having a thickness of 5 μm to 150 μm. In the adhesive sheet rolled out from the adhesive sheet roll, the peeling force Pl when the light peeling sheet is peeled off from the adhesive layer at a peeling angle of 180° and a peeling speed of 300 mm / min is 0.02 N / 25 mm to 0.30 N / 25 mm under an environment of 23° C. and a relative humidity of 50%, After peeling the light release sheet from the adhesive layer, a 50 μm polyethylene terephthalate film is attached to the exposed adhesive layer, and the heavy release sheet is further peeled from the adhesive layer at a peeling angle of 180° and a peeling speed of 300 mm / min under an environment of 23° C. and a relative humidity of 50%, and the peeling force Ph is 0.10 N / 25 mm to 0.80 N / 25 mm, Ph / Pl is 2 to 6, The thickness Tl of the light release sheet is 25 μm to 100 μm. The thickness Th of the heavy release sheet is 50 μm to 188 μm. And the Tl is less than the Th, The adhesive layer is formed using an adhesive composition containing an adhesive resin including a (meth)acrylic acid copolymer (a). The light release sheet and the heavy release sheet have release layers formed of a silicone release agent on the surfaces that are bonded to the adhesive layer. The light release sheet is placed on the outside of the roll.

2. The adhesive sheet roll according to claim 1, wherein The standard deviation σ of the thickness of the adhesive sheet is 10% or less relative to the layer thickness.

3. The adhesive sheet roll according to claim 1, wherein The adhesive layer is The gel fraction is 50% to 90% and the storage elastic modulus at -30°C is 10 MPa or less. The weight average molecular weight of the adhesive resin is 500,000 or more, The (meth)acrylic copolymer (a) is a copolymer having a structural unit derived from an alicyclic (meth)acrylate monomer and / or a structural unit derived from a linear or branched alkyl (meth)acrylate monomer having an alkyl group with 8 to 20 carbon atoms.

4. The adhesive sheet roll according to claim 1, wherein The thickness of the adhesive layer is 25 μm to 150 μm. The adhesive force of the adhesive layer is 10 N / 25 mm to 40 N / 25 mm with respect to the polyimide substrate.

5. The adhesive sheet roll according to claim 1, wherein The adhesive composition comprises a hardener, The curing agent is any one selected from the group consisting of isocyanate compounds, epoxy compounds, aziridine compounds, carbodiimide compounds, and metal chelate compounds.

6. The adhesive sheet roll according to claim 1, wherein The structural unit derived from an alicyclic (meth)acrylate monomer and / or the structural unit derived from a linear alkyl (meth)acrylate monomer having an alkyl group with 10 to 20 carbon atoms accounts for 10 to 75% by mass based on 100% by mass of the (meth)acrylic copolymer (a).

7. An adhesive sheet for a flexible display, which is produced by rolling out the adhesive sheet roll according to any one of claims 1 to 6 and performing a punching process.

Citation Information

Patent Citations

  • Roll-like adhesive sheet

    JP2021001272A

  • Roll-like adhesive sheet

    JP2021001273A

  • Adhesive sheet, using method of adhesive sheet, and manufacturing method of adhesive sheet

    CN103254828A

  • Substrate-free two-sided adhesive tape and manufacturing method thereof, and adhesive tape reel and manufacturing method thereof

    CN103360965A

  • Method for manufacturing laminate, adhesive roll and adhesive layer-containing laminated structure using laminate

    JP2014189659A